2020
DOI: 10.1016/j.hroo.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular paced activation in cardiac resynchronization therapy patients with left bundle branch block and relationship to its electrical substrate

Abstract: BACKGROUND Cardiac resynchronization therapy (CRT) uses left ventricular (LV) pacing to restore rapid synchronized LV activation when it is delayed in patients with myocardial disease. OBJECTIVE Although intrinsic LV activation delays are understood, little is known about reactions to LV stimulation and whether they are affected by QRS duration (QRSd), morphology, LV substrate, or choice of electrode pair. The purpose of this study was to test these interactions. METHODS In 120 heart failure patients with left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…This could be interpreted as electrical substrate modification by CRT being an independent factor from electrical substrate presence. The finding of electrical substrate modification being an independent factor aids the previous findings that LV‐paced conduction times by CRT are unrelated to baseline QRS morphology and that a poor correlation exists between intrinsic activation delay (qLV) and LV‐paced conduction time 9 . Also, another study reported that ΔQRS area was associated with event‐free survival independently from QRS morphology 10 .…”
Section: Discussionsupporting
confidence: 67%
“…This could be interpreted as electrical substrate modification by CRT being an independent factor from electrical substrate presence. The finding of electrical substrate modification being an independent factor aids the previous findings that LV‐paced conduction times by CRT are unrelated to baseline QRS morphology and that a poor correlation exists between intrinsic activation delay (qLV) and LV‐paced conduction time 9 . Also, another study reported that ΔQRS area was associated with event‐free survival independently from QRS morphology 10 .…”
Section: Discussionsupporting
confidence: 67%
“…This may be explained by the substantial but unpredictable differences in LV propagation seen on ECG imaging, despite pacing adjacent LV electrodes. 32 Therefore, we may conclude that the influence of a variety of factors on optimal LVLP is reflected by the large individual variation in paced effects and hemodynamics, and LVLP is highly patient-specific. Because measures of both LV dP/dt max and stroke work were consistent across all studies, these findings emphasize the need for individualized targeting of the optimal pacing site.…”
Section: Fallacy Of Empirical Lead Placement In Crt Rv Lead Position and Lv-only Pacingmentioning
confidence: 99%
“…39 Because of small differences in intrinsic activation delay when LVLP already is optimal, electrical indices such as LV-paced to RV-sensed wavefront propagation (ie, LVp-RVs) correlate poorly to QLV as well. 32 Therefore, LV-paced activation effects are highly unpredictable when based on stimulation site alone, despite widely variable acute electrical responses. 32,38 Where QLV is a measure of intrinsic electrical dyssynchrony, the difference between left and right paced-to-sensed interlead delays (LVp-RVs .…”
Section: Electrically Guidedmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 Moreover, these cannot be predicted from baseline QRS morphology or qLV. 3 The interaction of pacing and conduction barriers is important. When LV pacing facilitates conduction block, it will retard LV activation compared to intrinsic conduction ( Figure , middle).…”
Section: Discussionmentioning
confidence: 99%